MIRERC 027/2025; Gender Based Violence in Meru County, Kenya: Prevalence, Injury Characteristics, Health Facility Preparedness and Cost of Care - Aruyaru, Stanley Mwenda; Prof Salome Maswime, PhD; Prof Daniel K Ojuka, PhD; Dr. Oluchi Mbamalu,PhD, (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Background: Injury remains a leading cause of morbidity, mortality and disability adjusted life years across the world. Gender Based Violence (a subset of Interpersonal violence) with its various forms has negative impacts on physical heath, mental health, local and national economy and global sustainable development. Meru County, Kenya is among those counties with the leading cases of gender-based violence. Objective: To evaluate the prevalence, injury characteristics, Cost of Care and facility preparedness for Gender Based Violence care in Meru County of Kenya. Methods: This will be a multicentre mixed methods study across select level IV and V facilities in the study setting. Researcher-administered questionnaires will be utilized to extract data from level 4 and level 5 facilities in assessment of facility readiness and GBV prevalence. GBV prevalence assessed before and after introduction of a validated GBV screening tool. Injury characteristics will be collected from patient files through a preformed questionnaire while the cost of injury will be evaluated and by assessing the patient medical bills and extrapolated through financial modelling. Data analysis will be done through descriptive and inferential statistics and relevant statistical tests will be employed.